(Fig. VIII-1-14, Page 107-120) Visual characteristics of manganese nodules on bottom photographs collected in the Pacific Ocean during cruise GH77-1 of R/V Hakurei Maru - Kinoshita, Yasumasa; Moritani, Tomoyuki; Handa, Keiji (Supplement to: Kinoshita, Y et al. (1979): Manganese nodule occurrence and benthonic activities observed from deep sea photographs, in: Deep Sea Mineral Resources Investigation in the Central-Western Part of Central Pacific Basin, January-March 1977 (GH77-1 Cruise). Geological Survey of Japan, Cruise Report, 106-130, https://www.gsj.jp/data/cruise-rep/12-08.pdf, 1979)
Deep sea photographs in the GH77-1 cruise were obtained by two methods, namely a one-shot 16 mm camera attached to the freefall (boomerang) type photo grab and an independent 35 mm deep sea camera.